Effects of Different Intervention Factors on Vascular Endothelial Growth Factor-Induced Human Airway Smooth Muscle Cell Migration - Chengtian Lv; Guangyuan Liao; Lichan Wu; Jing Li; Yuanmei Gao (Canadian Respiratory Journal)
Background. Asthma airway remodeling is closely related to the abnormal migration of human airway smooth muscle cells (ASMCs), and vascular endothelial growth factor (VEGF) is involved in the pathophysiological process of asthma. This study aimed to investigate the effect of VEGF on ASMC migration through in vitro cell experiments and to intervene in ASMC migration with different asthma drugs and signaling pathway inhibitors to provide a basis for screening effective drugs for airway remodeling. Methods. The effect of VEGF on the proliferation of ASMCs was detected by the CCK-8 method, and the effect of VEGF on the migration of ASMCs was proven by scratch and transwell assays. Different asthma drugs and signaling pathway inhibitors were used to interfere with the migration of ASMCs. The number of migrating cells was compared between the intervention and nonintervention groups. Results. Our results showed that VEGF induction enhanced ASMC migration; pretreatment with the commonly used asthma drugs (salbutamol, budesonide, and ipratropium bromide) significantly attenuated VEGF-induced ASMC migration; and inhibitors SB203580, LY294002, and Y27632 blocked the VEGF-induced activation of p38 MAPK, PI3K, and ROCK signaling pathway targets in ASMCs and inhibited migration. Conclusion. This study shows that the current commonly used asthma drugs salbutamol, budesonide, and ipratropium have potential value in the treatment of airway remodeling, and the p38 MAPK, PI3K, and ROCK signaling pathway targets are involved in the VEGF-induced ASMC migration process. Signaling pathway inhibitor drugs may be a new way to treat asthma-induced airway remodeling in asthma patients in the future. However, the related mechanism and safety profile still need further research.